PENDIDIKAN BUDI PEKERTI DALAM KELUARGA, SEKOLAH DAN MASYARAKAT: Studi Kasus Pengembangan Model Pendidikan Budi Pekerti Terintegrasi pada Sekolah Dasar di Kota Malang. - Sulthoni, - (2010)
The number of cases such as mass affray, amoral behaviour, and the other life manners which had not reflected the culture values and the prevailing norms were what forming the background of this research. Commonly,the splendor of those deviate behavioursreferred to the degeneration ofawareness of character and moral, for that case the education in family, school, and society wasalso demanded for responsible aboutthatdemoralization. The morals education was the duty of family, school, and society. The morals education in family, school, and society, also the development of the morals education model in elementary school was based on theory and concept, including (1) The theory of education; (2) The concept of morals education; (3) The concept of family education; (4) The concept of society education; (5) The concept of value; (6) The theory of personality; (7) The concept of moral; (8) The theory of study. Those theories and conceptsgavedirection in the effort of morals education in family, school, and society, also to planned, done, and evaluated the morals education that was integrated in elementary school. This research was purposed to describe the role of parents, school, and society in implant the morals values and alsoin developingthe morals education model in elementary school. Afterwardsit's using the qualitative descriptive method and the class action research, and then the collection of data was done with interview, observation,the study of documentation and test. The result of this research hadindicated that (1) The role of parents in implant the morals value through the good religion education in house and societywith the habitual behaviour, good example, and giving the easy way, also the appreciation for the children achievement in carry outthemselves; (2) The role of schoolin implant the morals value get started from prepare the facility of study, the religious infrastructure (mushola), cleanliness, and the bound regulation. The headmaster, teachers, administration staff, security, and helper gave the good example of behavior so it can be listened, obeyed, and imitated. Extracurricular activity/ religious and the big day of national and religious is the medium of the effective morals education; (3)The role of society in develop the morals of children and teenager in their environment was giving the opportunity to them in filled the activity on the big day of national and religious, such as on August 17, mauludan, halal bi halal and the routine of Al-Quran recitation that was performed by the society figure including TPA/TPQ; (4)The continuity of morals education in family, school, and society was more harmony and dynamicgoing good; (5) The raising of the morals learning was integrated refer the change increasing of the study achievement value and the morals values. The conclusion this research is the morals education get started from family, school, and society environment was going on harmony, dynamic and in family atmosphere so it was getting on in the good way. As the closing of the research,writer recommends parents, school, and society to do phenomenological with communication, observation and good example that basis on love and for the next researcher can be developing this research more wide and deep.